Neighborhood Walkability and BMI Change: A National Study of Veterans in Large Urban Areas. Issue 1 (5th December 2019) - Tarlov, Elizabeth; Silva, Abigail; Wing, Coady; Slater, Sandy; Matthews, Stephen A.; Jones, Kelly K.; Zenk, Shannon N.
Abstract : Objective: Improving neighborhood walkability has been proposed as a policy intervention to reduce obesity. The objective of this study was to evaluate longitudinal relationships between neighborhood walkability and body weight among adults living in large urban areas. Methods: In this retrospective longitudinal study of United States military veterans using Department of Veterans Affairs health care, Veterans Affairs clinical and administrative data (2007‐2014) were linked to environmental measures constructed from public (2006‐2014) and proprietary (2008‐2014) sources, and linear regression models with person fixed effects were used to estimate associations between walkability and BMI among 758, 434 men and 70, 319 women aged 20 to 80 years in 2009 to 2014. Results: Neighborhood walkability was associated with small reductions in BMI. Effects were most pronounced among men aged 30 to 49 and 50 to 64. For women, differences were largest in the two youngest age groups, 20 to 29 and 30 to 49, though only estimates for all women combined were statistically significant. For women aged 30 to 49, effect sizes grew when the sample was limited to those who remained in the same neighborhood during the entire follow‐up period. Conclusions: Investments in the built environment to improve walkability may be a useful strategy for weight control in some segments of the adult population.